A description of human hydatid disease in Tasmania in the post‐eradication era. Issue 2 (22nd July 2013) - O'Hern, Jennifer A; Cooley, Louise
Abstract: Objective: To describe human hydatid disease in Tasmania since 1996, the year that the state was declared provisionally hydatid‐free. Design, setting and participants: Individuals with a new diagnosis or history of hydatid disease between January 1996 and July 2012 were identified through a number of sources including public health notifications, discharge coding from Tasmanian public hospitals, and the Royal Hobart Hospital pathology laboratory information system. Individuals were included if they fulfilled the case definition. Details regarding their diagnosis, management and risk factors were obtained by interview, review of medical notes, or both. The information was collected and analysed over a 3‐month period from 30 July 2012 to 30 October 2012. Main outcome measures: Patient demographics, site of infection, details of hydatid disease management and outcomes, time and place of likely hydatid acquisition, and public health notification. Results: Fifty‐one patients were identified, of whom 41 met the case definition. Twenty‐five represented new diagnoses between 1996 and 2012. Median age was 71 years (range, 44–99 years). There were 21 women and 20 men. Thirty‐eight patients had hepatic disease, five of whom had at least one other site involved. Four had extra‐abdominal disease. Twenty‐nine patients could be assessed for possible time and place of hydatid acquisition and all had significant risk factors for hydatid acquisition before 1980. Ten of the 25 patients diagnosed between 1996 and 2012 had been notified to the Tasmanian Department of Health and Human Services. Conclusion: We found no evidence of transmission of hydatid disease to humans following the provisional declaration of eradication of hydatid disease.